Migration And Remittances : Causes And Linkages - Niimi, Yoko (The World Bank, 2006)
The authors empirically examine the determinants of remittance flows at the cross-country level. They consider, among other things, the significance of the level of migration, the education level of migrants, and financial sector development in determining remittances. Given the potential endogeneity problems, the migration and financial development variables are instrumented in the estimation. They find that the migration level is the main driver of remittance flows, even after controlling for the endogeneity bias through instrumental variable estimation. The authors also find that the education level of migrants relative to the population in home countries, the size of the economy, and the level of economic development of recipient countries adversely affect remittance flows. While they find the effect of financial sector development to be positive, its significance is not strongly supported in their analysis